Managing adults with congenital heart disease in the catheterization laboratory: state of the art. (December 2010) - MacDonald, Simon T; Carminati, Mario; Chessa, Massimo
There has been a rapid growth in interventional cardiology techniques to treat adults with congenital heart disease, mirroring the rise of interventional cardiology as a cardiology subspecialty and the increasing population of adults with congenital abnormalities. Starting with neonatal balloon atrial septostomy for transposition of the great arteries in the 1960s, improving and changing percutaneous interventional techniques have increasingly replaced surgery as a treatment option in several congenital heart diseases. Many pediatric cardiac patients now survive to adulthood following early surgery, perhaps making additional surgery higher risk, and percutaneous procedures offer an alternative approach, although with a different inherent set of risks and benefits in terms of morbidity and mortality. Adult congenital heart disease patients offer distinct challenges such as unusual anatomy and demands such as pregnancy and exercise tolerability not found in conventional pediatric or traditional adult interventional patients. This article reviews current indications for adult congenital heart disease intervention and best practice, detailing the patient spectrum commonly treated, devices used and emerging treatments.